Pro Kontra Eksistensi Sajak Dalam Al-Qur’an - Yogi Suparman; Musfa Hendra; Zainuddin Soga (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Al-Qur'an (STIQ) ZAD Cianjur, 2021)
Differences in understanding in this concept give rise to various kinds of differences among scholars. One of them is the debate about the existence of rhymes (saja’) in the Qur'an, and this is a very classic problem. This debate had already arisen in the middle of the fourth century hijri spearheaded by imam Abul Hasan Al Asy'ari then popularized by imam Al Baqilani and imam Ar Rummani. These three high priests flatly rejected the existence of rhymes in the Qur'an and preferred the term fâshilah or fâwashil. On the other hand, the pro-life in this matter, such as the mu'tazilah figures, remained adamant in defending their opinions and presenting arguments that he considered strong. Therefore, this paper tries to find common ground and tries to take a middle ground from these differences, because there are points of similarity in them so that it is very possible to combine and collaborate. Among the results of this study is that the term fâshilah is more common than the term rhyme (saja’). So the consequence is an opinion that chooses the term fâshilah for the naming of each end of the verse, indirectly acknowledging the existence of rhymes (saja’) in the Qur'an. Because the rhyme (saja’) itself is part of the fâshilah that is in the Qur'an.